Method for Collecting Pasture Ticks by Cylinder-Shaped Drags - A. D. Reshetnikov; A. I. Barashkova (Российский паразитологический журнал)
The purpose of the research is developing a method to collect pasture ticks where their number is small.Materials and methods. The work was done in 2013–2016. The patent search was conducted according to the task and the search schedule. We found sufficient literature sources and protection documents on the investigated issue. Investigational studies were performed to design an instrument to collect pasture ticks.Results and discussion. A method was developed to collect pasture ticks where their number is small. In order to do this, an instrument was designed which had a cylinder shape and was covered with a cloth called a drag. A rod was placed through the cylinder axle, having its ends connected to each other with a cord to drag the cylinder on the grass. Cylinder rotation when dragged through the grass brings the cloth in contact with ticks without being displaced in relation to one another. A patent of the Russian Federation was obtained under number No. 2544088 “Method for Collecting Ticks”.